PENGEMBANGAN MEDIA PEMBELAJARAN DENGAN MENGGUNAKAN GOOGLE SITES DALAM PEMBELAJARAN TEKS BIOGRAFI KELAS X SMA - Hapsary Ratnadewati; riswanda Himawan; Hermanto (Jurnal Lingkar Mutu Pendidikan, 2023)
The development of technology and information in this era certainly affects the increasingly advanced learning media, but not all learning activities use modern and up-to-date learning media. Based on this, researchers are interested in developing learning media based on Google Sites in learning biographical texts for class X at MA Muhammadiyah 1 Yogyakarta. In this study, researchers used a research and development (R&D) research model with the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). The research technique used is interview and questionnaire technique. This study obtained data sources from a team of experts (material experts, media experts, and teaching experts (teachers)) and user groups (students). The results of this study stated that the development of learning media based on Google Sites in the biographical text of class X SMA / MA obtained "Very Eligible" results with an average score of 81.71. The average score obtained from the assessment of the expert team and media users (students). The score of material expert is 81.6, media expert is 80, teaching expert (teacher) is 80, and the result of limited trial (student) is 85.25. Based on the results of the assessment, it can be concluded that the Google Sites-based learning media in the biographical text material for class X KD 3.14 and 4.14 "Very Eligible" is used as a learning medium.